Numerical analysis of the two‐phase steam‐air heat transfer flow induced in smooth and corrugated channel using the VOF model. Issue 8 (12th August 2022) - Koulali, Aimad
Abstract: In this paper, heat transfer induced in smooth and wavy channels in the presence of two phases (air and steam) was conducted and discussed. Two configurations have been studied according to the geometrical shape of the channel walls. The thermal and hydrodynamic fields in the channel have been predicted using the single‐fluid approach with a solver based on the finite volume method. Explicit formulation of the volume of fluid was used to track the interface between both fluids. The mesh in the wavy channel was treated with a curvilinear mesh grid. Local Nusselt evolution, isothermal distribution, streamlines, and other parameters have been shown at different times of simulation. It was found that weak air phase velocities and wave patterns of the channel walls play a destabilizing role in the interface evolution between both fluid phases. In addition, results show that channels with wavy walls can be an effective solution to ensure higher heat transfer in two‐phase flows.